2013
DOI: 10.1002/pds.3432
|View full text |Cite
|
Sign up to set email alerts
|

Kidney function decline in metformin versus sulfonylurea initiators: assessment of time‐dependent contribution of weight, blood pressure, and glycemic control

Abstract: Background and objective-We recently reported that kidney function declined faster among initiators of sulfonylureas compared to metformin; however, sulfonylurea compared to metformin use was also associated with increases in body mass index (BMI) and systolic blood pressure (SBP). We sought to determine if differences between sulfonylureas and metformin on kidney function decline were mediated by differential effects on BMI, SBP, or glucose control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 59 publications
3
37
0
1
Order By: Relevance
“…Those receiving metformin reported lower risk of kidney disease progression when compared to sulfonylurea. The aforementioned finding was independent of body mass index, systolic blood pressure and glycosylated hemoglobin . A separate study of patients with PCOS also demonstrated no adverse affect on kidney function with metformin …”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Those receiving metformin reported lower risk of kidney disease progression when compared to sulfonylurea. The aforementioned finding was independent of body mass index, systolic blood pressure and glycosylated hemoglobin . A separate study of patients with PCOS also demonstrated no adverse affect on kidney function with metformin …”
mentioning
confidence: 72%
“…We already know that metformin dose reduction and adequate hydration are key components to guard against kidney injury and lactic acidosis in those with kidney disease. The safety of metformin is further exemplified in a study of over 13,000 veterans initiated on either a sulfonylurea or metformin and followed for more than a decade . Those receiving metformin reported lower risk of kidney disease progression when compared to sulfonylurea.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 However, it is also important to consider the specific disadvantages of the alternative treatment options. Although the treatment of diabetes is evolving, many agents are contraindicated or unlicensed for use in advanced CKD.…”
Section: Disadvantages Of Other Treatment Optionsmentioning
confidence: 99%
“…Metformin initiation has been shown to be associated with a lower risk of decline in kidney function or death compared to sulfonylureas independent of changes in body mass index and systolic blood pressure and glycated haemoglobin over time [66]. …”
Section: Renoprotective Effect Of Metformin In Human In Retrospectivementioning
confidence: 99%